Preparation and Loading with Rifampicin of Sub-50 nm Poly(ethyl cyanoacrylate) Nanoparticles by Semicontinuous Heterophase Polymerization. (20th July 2016) - Saade, H.; Barrera, C.; Guerrero, R.; Mendizábal, E.; Puig, J. E.; López, R. G.
Abstract : We report the preparation of poly(ethyl cyanoacrylate) (PECA) nanoparticles by semicontinuous heterophase polymerization carried out at monomer starved conditions at three monomer addition rates. Particles in the nanometer range were obtained, the size of which diminishes with decreasing monomer addition rate as shown by the fact that particles with mean diameters of ca. 42 and 30 nm were obtained at the faster and intermediate dosing rates, respectively, whereas two populations of particles, one of 15.5 and the other of 36 nm in mean diameters, were produced at the slower dosing rate. The obtained molecular weights were from 2, 200 to 3, 500 g/mol, depending on the addition rate, which are typical of the anionic polymerizations of cyanoacrylates in aqueous dispersions at low pHs. The rifampicin (RIF) loading into the nanoparticles was successful since the entire drug added was incorporated. The drug release study carried out at pH of 7.2 indicated a faster release from the free RIF at intermediate and larger release times as expected since, in the nanoparticles, first the drug has to diffuse through the nanoparticle structure. The comparison of several drug release models indicates that the RIF release from PECA nanoparticles follows that of Higuchi.